(untitled) (Public Sector Economics - submission site, 2020)
This paper analyses the effects of a recently introduced capital gains tax on the trading volume on the Zagreb Stock Exchange. Using three different methodological approaches – event study methodology, regression discontinuity design and panel regressions – we offer evidence that the introduction of the capital gains tax in January 2016 created abnormally high trading volume patterns shortly before the tax came into force and abnormally low volume patterns after the fact, further decreasing the liquidity of an already poorly liquid market. The negative effects are significant in both the short and the longer term, as our difference-in-differences estimations suggest that the average trading volume in the three post-tax years decreased by 23% vis-à-vis the pre-tax period.